STUDY ON THE ESTIMATION OF SARS-CoV-2 VIRUS PATHOGENS’ TRANSMISSION PROBABILITIES FOR DIFFERENT PUBLIC BUS TRANSPORT SERVICE SCENARIOS - Rafał BURDZIK; Niko SPEYBROECK (Transport Problems)
The worldwide COVID-19 pandemic revealed societal challenges, with passenger transport rapidly experiencing the impacts of the virus and the evolution of the concept of safety in transport. Evaluating the likelihood of viral transmission within transportation systems may be a substantial challenge, considering the complex processes that influence the incidence of random transmission events. This paper introduces a method for determining the probability of pathogen transmission in public transport, focusing on the SARS-CoV-2 virus. The study draws on scenarios from the first and second waves of the COVID-19 pandemic in Poland, a period that was devastatingly marked by the lack of available vaccines. This study aims to add value to the scientific community by offering an estimation of the likelihood of SARS-CoV-2 transmission in public transport and a preliminary risk assessment for COVID-19 infection, considering the number of active, non-isolated COVID-19 cases in the Polish population. The potential of this approach was demonstrated through a comparison between two different categories of passenger transport in a city bus. Based on the presented case study and the calculated probability of pathogen transmission, it is estimated that the probability of SARS-CoV-2 infection during the second wave of the COVID-19 pandemic in Poland through the use of public transport was approximately 0.05%. Probability estimations based on elementary events, which can vary depending on the service category (for instance, the form of ticket purchase, availability of seating or standing places, or ticket inspection), can reveal even the smallest differences in the total likelihood of pathogen transmission. However, these minute individual variations significantly impact the total metrics calculated for daily users of public transport. For effective monitoring of potential epidemic threats and for designing suitable interventions and restrictions to lower the risk of future pandemics, it may be necessary to understand the role that transportation systems, particularly public transport systems, play in the spread of pathogens.